A Novel Approach for Differential Electrochemical Mass Spectrometry Studies on the Decomposition of Ionic Liquids. (10th April 2016) - Alwast, D.; Schnaidt, J.; Law, Y.T.; Behm, R.J.
Graphical abstract: Abstract: We report on a novel differential electrochemical mass spectrometry (DEMS) set-up, which allows us the online detection of volatile products formed during potential induced decomposition of ionic liquids, and its application for elucidating the decomposition mechanism of the two ionic liquids (ILs) 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)amide ([BMP][TFSA]) and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide ([EMIM][TFSA]) on polycrystalline Au electrodes. In the cathodic scan, the [BMP] + cation decomposes at potentials more negative than −1.0 V vs. Ag/AgCl by cleaving the butyl side chain, below −2.6 V also ring opening takes place. For [EMIM][TFSA] reduction, we find a decomposition product which based on its mass is compatible with a stable imidazolium radical appearing at −2.3 V, accompanied by its saturated derivative. In the anodic scan the [TFSA] − anion is decomposed first for both ILs, possible decomnposition products are discussed.